2005
DOI: 10.1007/s11284-005-0041-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant responses to elevated CO2 concentration at different scales: leaf, whole plant, canopy, and population

Abstract: Elevated CO 2 enhances photosynthesis and growth of plants, but the enhancement is strongly influenced by the availability of nitrogen. In this article, we summarise our studies on plant responses to elevated CO 2 . The photosynthetic capacity of leaves depends not only on leaf nitrogen content but also on nitrogen partitioning within a leaf. In Polygonum cuspidatum, nitrogen partitioning among the photosynthetic components was not influenced by elevated CO 2 but changed between seasons. Since the alteration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…However, more and more studies have shown that other environmental factors (e.g. soil fertility, soil water availability) could regulate plant responses to rising CO 2 (Oren et al 2001;Prior et al 2003;Hikosaka et al 2005). Wand et al (1999) and Ward et al (1999) showed that soil water and nutrient stress reduced the response of C 3 , but not C 4 plants, to CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, more and more studies have shown that other environmental factors (e.g. soil fertility, soil water availability) could regulate plant responses to rising CO 2 (Oren et al 2001;Prior et al 2003;Hikosaka et al 2005). Wand et al (1999) and Ward et al (1999) showed that soil water and nutrient stress reduced the response of C 3 , but not C 4 plants, to CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…This could influence the water balance by increasing evapotranspiration and decreasing runoff. In addition, at the canopy scale, the evapotranspiration effect of increased LAI can be masked by shading among leaves, soil cover and raised canopy humidity (Hikosaka et al, 2005;Bunce, 2004). A study that considered both effects suggested that the fertilization effect of rising CO 2 is larger than the stomatal pore reduction effect, and the net effect is decreases in runoff (Piao et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated [CO 2 ] may cause short-term increases in vegetative growth due to higher rates of CO 2 assimilation, and these increases in growth might translate into an increase in male fitness. This positive response might decrease over time if there is a downward regulation of photosynthesis or if other resources become limited (Conroy and Hocking 1993;Geiger et al 1999;Urban 2003;Hikosaka et al 2005). To address these issues, we examined how [CO 2 ] affected male components of fitness in wild radish over several months.…”
Section: Discussionmentioning
confidence: 99%